Frequencies of multiple paternity in three Acrocephalus species (Aves Sylviidae) with different mating systems (A. palustris, A. arundinaceus, A. paludicola) - Leisler, Bernd; Wink, Michael (Ethology, ecology & evolution, 2010)
Genetic parentage was determined by DNA-fingerprinting with multilocus probes and microsatellite PCR in three Acrocephalus species with different mating systems: the socially monogamous marsh warbler (A. palustris), the polygynous great reed warbler (A. arundinaceus) and the promiscuous aquatic warbler (A. paludicola). The amount of extra-pair paternity (EPP)/multiple paternity (MP) was then related to ecological parameters (increasing productivity) and parental care (decreasing male participation) of Acrocephalus species. Marsh warblers (33 broods, 131 young plus putative parents) were studied over 3 years in a German population. No case of social polygyny but four extrapair young (EPY) were detected in three socially monogamous broods. The low frequency of extra-pair fertilization (EPF, 9.1% of broods, 3.1% of offspring) may be best attributed to intense male mate-guarding and restrictions on mate assessment due to an extremely short breeding window. The rate of social polygyny in a German great reed warbler population varied between 8 and 35% of males during a 5-year period. In 48 broods (27 monogamous and 21 polygynous males) with 194 young, 5 nests (3 of polygynous, 2 of monogamous males) with 19 EPY were recorded: EPF-rates are 10.4% of broods and 9.8% of offspring. In none of the nests were neighbouring males the genetic fathers, but in 2 nests, “bachelor” males from distant territories had sired the offspring. The EPP-rate in this species seems to be related to an incomplete correlation between male and territory characteristics leaving some females to correct their choice. Aquatic warblers were studied during three years in a Polish population. In each of the years, MP was recorded in more than half of a total of 75 broods (mean 76%). The proportion out of 340 young sired by one to five “additional” males varied between 25 and 57% (mean 39.1%). Food resources are neither critical nor economically defendable in the species' habitat and paternity assurance behaviours of males and female choice are yet not fully understood.